HOTS-Based Islamic Education Learning (Study at MTs Negeri 2 Palembang on Fiqh Subject) - Ermis Suryana; Nazarudin Nazarudin (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
The results of the PIRLS, PISA and TIMSS studies show that the reading skills of Indonesian students are still relatively low. While we know that one of the indicators of critical thinking skills is the high interest in reading, this is certainly a universal problem. With this problem, one of the changes that must be made is to revise the curriculum elements themselves, including the learning process. It is necessary to strengthen the learning process that can improve the quality of learning more effectively, efficiently, enjoyably, and meaningfully, so as to improve the quality of achievement of learning outcomes and prioritize students' critical thinking (not just conveying factual). This article tries to examine the implementation of HOTS-based PAI learning by focusing on Fiqh subjects at MTsN 2 Palembang. This research uses a qualitative research approach, and data collection methods through interviews and documentation. The results showed that HOTS-based Fiqh learning at MTsN 2 Palembang is based on several indicators, namely: planning, implementation and evaluation Planning begins with creating a HOTS Guidebook with the 3M concept and formulating HOTS-based lesson plans starting from the even semester of the 2018-2019 academic year with PPK and 4C content. While in the implementation, teachers prepare students to reach the HOTS level by starting with apperception in the scope of C1 (memorization), C2 (understanding), and C3 (application). The model used in HOTS-based learning is problem-based instruction. The teacher gives problems about Fiqh material to students in the form of group or individual problems. Students analyze, assess, and make decisions and conclude to present the results of their work. And the evaluation carried out by the teacher is in the form of daily tests, holistic assessment (AH), end-of-semester assessment (PAS), and end-of-year assessment (PAT).